A bipartite DNA binding domain composed of direct repeats in the TATA box binding factor TFIID. - Yamamoto, T (1992)
Point mutations in residues comprising the interrupted direct repeats of TFIID eliminated DNA binding in an electrophoretic mobility shift assay. In contrast, mutations in nonconserved residues within the direct repeat regions or in lysine residues comprising the intervening basic repeat had no effect on DNA binding. However, small spacing changes (addition or deletion of one to three residues) in the basic repeat eliminated DNA binding. These results argue for a bipartite DNA binding domain composed of direct repeats with a strict spacing and orientation. Surprisingly, some direct repeat mutations that inhibited DNA binding failed to show a corresponding inhibition of basal transcription, indicating compensating interactions of TFIID with other general factors. The implications of these and other recent results for TFIID structure, promoter recognition, and interactions with other factors are discussed.